1995
DOI: 10.1128/jb.177.1.229-234.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of 6-chlorohydroxyquinol 1,2-dioxygenase from Streptomyces rochei 303: comparison with an analogous enzyme from Azotobacter sp. strain GP1

Abstract: The enzyme which cleaves the benzene ring of 6-chlorohydroxyquinol was purified to apparent homogeneity from an extract of 2,4,6-trichlorophenol-grown cells of Streptomyces rochei 303. Like the analogous enzyme from Azotobacter sp. strain GP1, it exhibited a highly restricted substrate specificity and was able to cleave only 6-chlorohydroxyquinol and hydroxyquinol and not catechol, chlorinated catechols, or pyrogallol. No extradiolcleaving activity was observed. In contrast to 6-chlorohydroxyquinol 1,2-dioxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
56
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 26 publications
6
56
1
Order By: Relevance
“…For bacteria, it has been shown that maleylacetate reductases are involved in the degradation of resorcinol and 2,4-dihydroxybenzoate via hydroxyquinol (Larway & Evans, 1965;Chapman & Ribbons, 1976;Stolz & Knackmuss, 1993). Other substrates whose catabolic routes comprise this activity have a more complex structure, such as 2-hydroxydibenzo-p-dioxin and 3-hydroxydibenzofuran (Armengaud et al, 1999), or carry unusual substituents, such as nitro or sulfo groups (Spain & Gibson, 1991;Feigel & Knackmuss, 1993;Jain et al, 1994;Rani & Lalithakumari, 1994), fluorine or chlorine atoms (Duxbury et al, 1970; Schlömann et al, 1990a;Latus et al, 1995;Zaborina et al, 1995;Daubaras et al, 1996;Miyauchi et al, 1999).The maleylacetate reductase genes characterized so far tend to belong to specialized gene clusters for the degradation of aromatic compounds. Thus, 3-hydroxydibenzofuran and 2-hydroxydibenzo-p-dioxin degradation via hydroxyquinol appears to be encoded by a specialized gene cluster comprising most of the genes for the pathway including a maleylacetate reductase gene (Armengaud et al, 1999).…”
mentioning
confidence: 99%
“…For bacteria, it has been shown that maleylacetate reductases are involved in the degradation of resorcinol and 2,4-dihydroxybenzoate via hydroxyquinol (Larway & Evans, 1965;Chapman & Ribbons, 1976;Stolz & Knackmuss, 1993). Other substrates whose catabolic routes comprise this activity have a more complex structure, such as 2-hydroxydibenzo-p-dioxin and 3-hydroxydibenzofuran (Armengaud et al, 1999), or carry unusual substituents, such as nitro or sulfo groups (Spain & Gibson, 1991;Feigel & Knackmuss, 1993;Jain et al, 1994;Rani & Lalithakumari, 1994), fluorine or chlorine atoms (Duxbury et al, 1970; Schlömann et al, 1990a;Latus et al, 1995;Zaborina et al, 1995;Daubaras et al, 1996;Miyauchi et al, 1999).The maleylacetate reductase genes characterized so far tend to belong to specialized gene clusters for the degradation of aromatic compounds. Thus, 3-hydroxydibenzofuran and 2-hydroxydibenzo-p-dioxin degradation via hydroxyquinol appears to be encoded by a specialized gene cluster comprising most of the genes for the pathway including a maleylacetate reductase gene (Armengaud et al, 1999).…”
mentioning
confidence: 99%
“…The breakdown of mono-or dichlorophenols is usually through a catechol intermediate before ring cleavage (6). On the other hand, most polychlorinated phenols are degraded through a chlorohydroxyquinol (CHQ) intermediate before ring cleavage (1,3,24).The reaction mechanisms and enzymes responsible for the degradation of polychlorinated phenols have been studied in several microorganisms (11,20,(22)(23)(24). Flavobacterium sp.…”
mentioning
confidence: 99%
“…The breakdown of mono-or dichlorophenols is usually through a catechol intermediate before ring cleavage (6). On the other hand, most polychlorinated phenols are degraded through a chlorohydroxyquinol (CHQ) intermediate before ring cleavage (1,3,24).…”
mentioning
confidence: 99%
“…Second, the degradation of the dihydroxylated benzene derivatives involves ring fission and subsequent reactions linked to central metabolism in the cell. Ring fission is catalyzed by ring-cleavage dioxygenases that use molecular oxygen to open the aromatic ring between the two hydroxyl groups (ortho-cleavage, catalyzed by intradiol dioxygenases) 39,40) or proximal to one of the two hydroxyl groups (meta-cleavage, catalyzed by extradiol dioxygenases) 11,17,35) . For many years, investigations of the degradation of aromatic compounds have focused almost exclusively on Gram-negative bacteria such as species of Pseudomonas and a considerable body of knowledge has emerged 23) .…”
mentioning
confidence: 99%